2005
DOI: 10.1021/ic0484396
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural Characterization, and Computational Studies of Novel Diiodine Adducts with the Heterocyclic Thioamides N-Methylbenzothiazole-2-thione and Benzimidazole-2-thione:  Implications with the Mechanism of Action of Antithyroid Drugs

Abstract: Reaction of N-methylbenzothiazole-2-thione (C8H7NS2 or NMBZT) with diiodine produced the charge-transfer (ct) complex [(NMBZT).I2] (1). NMBZT reacts with diiodine in the presence of FeCl3 in a molar ratio of 3:6:1 and forms the ionic complex [[(NMBZT)2I+].[FeCl4]-] (2) together with [[(NMBZT)2I+].[I7]-] (2a) iodonium salt. The reaction of benzimidazole-2-thione (C7H6N2S or MBZIM) with diiodine on the other hand results in the formation of the ct [[(MBZIM)2I]+[I3]-].[(MBZIM).I2] (3) compound. The compounds have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 29 publications
(69 reference statements)
2
47
0
Order By: Relevance
“…An extensive investigation on tertiary phosphines (and arsines)-dihalogen adducts has been performed by the McAuliffe group, who has disclosed their peculiar reactivity towards crude inactivated metal powders to form metal complexes of metals in high oxidation states [17]. CT complexes, which play an important role in many red-ox reactions [18], may be described as "intermediates" sufficiently stable to be isolated, and attempts to correlate structural changes with the dynamic of reacting chemical species have been performed for a long time [19], but no systematic kinetic study addressed to find a general reaction mechanism for these reactions is available. It has been found remarkably that R 3 D·I 2 (R = Alkyl; D = As, P) are capable of oxidizing even a noble metal such as gold in a one-step reaction, as summarized in Scheme 3 [20].…”
Section: σ-Donor/dihalogen Adductsmentioning
confidence: 99%
“…An extensive investigation on tertiary phosphines (and arsines)-dihalogen adducts has been performed by the McAuliffe group, who has disclosed their peculiar reactivity towards crude inactivated metal powders to form metal complexes of metals in high oxidation states [17]. CT complexes, which play an important role in many red-ox reactions [18], may be described as "intermediates" sufficiently stable to be isolated, and attempts to correlate structural changes with the dynamic of reacting chemical species have been performed for a long time [19], but no systematic kinetic study addressed to find a general reaction mechanism for these reactions is available. It has been found remarkably that R 3 D·I 2 (R = Alkyl; D = As, P) are capable of oxidizing even a noble metal such as gold in a one-step reaction, as summarized in Scheme 3 [20].…”
Section: σ-Donor/dihalogen Adductsmentioning
confidence: 99%
“…While halogen bonding involving the halogenated thyroid enzymes is often the focus of studies in this area, the role of I 2 is also of interest [17,18]. Closely related to this are investigations into the interaction of various antithyroid drugs with I 2 [19]. Recently, it has also been found that certain psychotropic drugs also affect thyroid function, with halogen bonding potentially playing a major role [20].…”
Section: Significance Of Halogen Bonding With Dihalogensmentioning
confidence: 99%
“…Since then, a large number of such complexes have been studied. This interest has been driven in large part by research in two areas: the unusual electric properties imparted to materials when doped with dihalogens (particularly iodine) [55], and the study of dihalogen and interhalogen complexes with potential antithyroid drugs and related derivatives, including dithiole thiones [56][57][58][59][60][61][62][63][64][65], imidazole thiones [19,[66][67][68][69][70][71][72][73] and selones [68,[74][75][76], thiazole thiones [77] and selones [78][79][80], oxazole thiones [81], and various thiourea derivatives [77,82]. Additional activity has involved the fundamental study of halogen bonding in particular classes of compounds, such as aromatic nitrogen heterocycles [31,[83][84][85][86][87][88][89][90][91][92][93][94]96], thioether...…”
Section: General Observationsmentioning
confidence: 99%
“…They also present a great deal of interest from the purely scientific point of view as two electronic structures of different connectivity and stability are possible to be formed, the charge transfer (CT) complexes bearing a linear E-X-Y arrangement and the hypervalent T-shaped adducts presenting a X-E-Y geometry [7,8]. The many crystallographic and theoretical investigations carried out on these systems [9][10][11][12][13][14] have revealed quite interesting correlations between the kind of the adduct formed and its various physicochemical properties from one side and the electronegativity of the halogen and the feasibility for the LEX + +Y À dissociation channel on the other [15,16]. The formation of T-shaped adducts was suggested to prevail if the electronegativity value of the halogen is higher than that of E, while charge transfer (CT) adducts are formed in the reverse case.…”
Section: Introductionmentioning
confidence: 99%